Toward Well-Oiled Relations? China's Presence in the Middle East following the Arab Spring - Horesh, Niv (The Nottingham China Policy Institute Series, 2016)
With China replacing the United States as the world's leading energy user and net oil importer, its relations with the Middle East is becoming a major issue with global implications. Horesh and his contributors set out to analyse the implications of China's growing presence in the Middle East.